High Incidence of Echocardiographic Abnormalities of the Interatrial Septum in Patients Undergoing Ablation for Atrial Fibrillation. Issue 4 (10th December 2012) - Schernthaner, Christiana; Danmayr, Franz; Daburger, Apollonia; Eichinger, Jörg; Hammerer, Matthias; Strohmer, Bernhard
<x xml:space="preserve">Abstract</x> Background: Atrial fibrosis or fatty deposition is known to increase the propensity for the development of atrial fibrillation (AF). Apart from the pulmonic veins, the interatrial septum (IAS) might play a role in the maintenance of AF. In contrast to left atrial anatomy and adjacent veins, the IAS cannot be visualized in detail with computed tomography. Thus, preprocedural transesophageal echocardiography (TEE) may provide important morphologic information beyond exclusion from atrial thrombi. Methods: The study comprised 108 consecutive patients (mean age 60 ± 11 years; 98 men). AF was paroxysmal in 91 (84%) and persistent in 17 (16%) patients. We investigated the morphological characteristics of the IAS by TEE in patients who underwent radiofrequency ablation of AF. Results: The IAS was structurally abnormal in 46 (43%) patients, showing the following echocardiograhic findings: atrial septal hypermobility or aneurysm (n = 27) associated with a patent foramen ovale (PFO) (n = 11) or with a small atrial septal defect (ASD) (n = 2), a septal flap associated with a PFO or an ASD (n = 8), and an abnormally thickened IAS (n = 12). A thrombus in the left atrial appendage was discovered in only 2 (2%) patients. Conclusions: A structurally abnormal IAS was diagnosed in nearly half of the patients undergoing ablation therapy for AF. The information obtained by TEE is mandatory to exclude left atrial thrombi prior the ablation procedure. Moreover, detailed knowledge of morphologic characteristics of the IAS facilitates an optimized and safe performance of the transseptal puncture using long sheaths with large diameters.